Al-Qur'an Solutions in Internal and External Moderation of Religious People in Indonesia - Daruhadi, Gagah (International Journal Labs, 2024)
This study aims to find out the religious moderation teachings of Nahdlatul Ulama (NU) and Muhammadiyah in the concept of Nusantara Islam and Progressive Islam and its relationship with the verses of the Qur'an. The study employs a qualitative-descriptive research approach, focusing on observable human behavior and using library research methods to gather primary, secondary, and tertiary materials. The research contributes by examining how these guidelines can be applied both within the Muslim community and in interactions with people of other religions. The results of the research show that, from outside Islam, the Prophet Muhammad brought the teachings rohmatan lil 'alamin. In addition, examining the role of interfaith dialogue in enhancing religious tolerance and cooperation could provide insights into overcoming existing challenges.